Effect of Instagram Ads on Consumer Purchase Interest in Skin Care - Rudianto, Rudianto; Ekasari, Silvia; Beryansyah, Beryansyah; Purwanti, Purwanti; Munizu, Musran (LPPPIPublishing, 2024)
The development of digital media has created innovative changes and opportunities in the field of marketing. If social media is used and used correctly, marketing through social media can clearly reduce marketing costs in the long run. A real example is Instagram advertising, which tends to be cheaper and more effective than other search engine advertising options. Advertisements can be defined as messages that offer a product aimed at the public through an information medium. This research aims to analyze effect of instagram ads on consumer purchase interest in skin care. This type of research is descriptive quantitative research. Population in this think about is the number of consumer purchase interest in skin care as Instagram users. Sample of tests for this consideration is 50 consumer purchase interest in skin care as Instagram users. The data analysis method used simple linear regression analysis. The results show that Instagram ads has significant effect on consumer purchase interest.